Pengembangan E-Module Berbasis Flip PDF Professional Terhadap Hasil Belajar Siswa Pada Tema 5 Kelas III SD Negeri 018445 Hessa Perlompongan - Hardini, Juria; Simanjuntak, Sorta; Simanjuntak, Eva Betty; Faisal, Faisal; Siregar, Waliyul Maulana (Journal of Computer Science and Information System(JCoInS), 2023)
The purpose of this research is to determine the validity, practicality and effectiveness of professional flip pdf based e-modules. This research method is the ADDIE development model. The data collection used was interviews, questionnaires and test instruments. The data analysis techniques used are qualitative and quantitative. Validation was carried out by material experts, media experts and practitioner experts by class III educators. The results of the analysis show that the product developed in the form of an e-module falls into the very feasible category. Based on validation: 1) Learning material experts get an average percentage of 85%; 2) Learning Media Expert with an average percentage of 81%; 3) Expert Practitioner with an average percentage of 92%. And continued with the distribution of Pre-Test and Post-Test questions to Class III with a total of 20 students, an average Pre-Test score of 56.5 was obtained, increasing from the average Post-Test result of 85.75. From the data obtained, it can be concluded that the professional flip pdf based e-module developed is effective in improving learning outcomes.